Gender- and age-stratified analyses of gambling disorder in Finland between 2011 and 2020 based on administrative registers - Salonen Anne H; Castrén Sari; Latvala Tiina A; Grönroos Tanja; Levola Jonna; Vuori Miika (Sage, 2022)
Aim: Prevalence studies on gambling have largely relied on survey samples. Little is known about the diagnosed prevalence of gambling disorder (GD) based on register data. This study examines the annual prevalence rate of GD between 2011 and 2020 among Finns by gender and age.
Methods: Aggregated data on the diagnosis of GD (corresponding to pathological gambling, code F63.0 in the ICD-10) were retrieved from the following national registers: Register of Primary Health Care Visits, and Care Register for Health Care, including specialised outpatient and inpatient health care, and inpatient Care Register for Social Welfare. Primary and secondary diagnoses of adults were included. Average population during a calendar year (4,282,714-4,460,177 individuals) was utilised to calculate annual prevalence.
Results: The annual prevalence of diagnosed GD in the population increased from 0.005% (n = 196) to 0.018% (n = 804) within nine years. In 2011, the annual prevalence rate was 0.006% for men and 0.003% for women, compared to rates in 2020 of 0.025% and 0.011%. Gender discrepancy was relatively stable across years: 27.2-33.8% of the diagnoses were for women. The prevalence of GD varied between age groups within genders. GD was most prevalent among 18-44-year-olds. The prevalence rates increased the most among 30-44-year-old women.
Conclusion: The extremely low prevalence rate of GD implies that the problem remains under-diagnosed, yet, it has increased among all age groups across genders, except for women aged 60 years or older. Active efforts are needed to increase awareness of GD among both primary and specialised healthcare professionals and the public for better recognition and early detection.